Low Loss Microwave Ceramic and other Microwave Dielectric Materials for Beam Physics Applications - Alexei D. Kanareykin (Известия высших учебных заведений России: Радиоэлектроника, 2019)
Introduction. Relativistic, high intensity and small emittance electron bunches are the basis of a future linear collider and free electron laser projects. Drive beam generation in a wakefield structure employing for power extraction and acceleration low loss dielectrics like microwave ceramics, fused silica and Chemical Vapor Deposition (CVD) diamond were considered.Objective. We report here our experimental testing of a ceramic material with extremely low loss tangent at GHz frequency ranges allowing the realization of high efficiency wakefield acceleration. We also present Barium Strontium Titanium oxides (BST) ferroelectric material, which is a critical tuning element of the 400 MHz superconducting radiofrequency (RF) tuner developed and tested by the CERN/Euclid Techlabs collaboration. The materials discussed here also include quartz and CVD diamonds that are capable of supporting the high RF electric fields generated by electron beams or pulsed high power microwaves. These materials have been optimized or specially designed for accelerator applications.Materials and methods. The ceramic materials for accelerators, commonly used for the dielectric based accelerating structures, have to withstand high gradient accelerating fields, and prevent potential charging by electron beams. Correspondingly, the ceramic materials, fused silica and CVD diamond were tested with high power wakefield accelerating structures at Argonne Wakefield Accelerator of Argonne National Laboratory. Some of the presented here ceramic materials were tested at X-band 11.4 GHz magnicon high power source.Results. Low loss microwave ceramics, fused silica, and CVD diamonds have been considered as materials for dielectric based accelerating structures to study of the physical limitations encountered driving > 100 MV/m at microwave and ~ GV/m at THz frequencies in a dielectric based wakefield accelerator. Various ceramic compositions were high power and electron beam tested at X-band 11.4 GHz magnicon power source and Argonne Wakefield Accelerator correspondingly. Special attention was paid to the CVD diamond cylindrical Ka-band 35 GHz wakefield structure development. Finally, the dielectric based structure tuning was demonstrated by varying the permittivity of the BST ferroelectric layer by temperature changes and by applying an external direct current electric field across the ferroelectric. This allows us to control the effective dielectric constant of the composite system and therefore, to control the structure frequency during operation. The same type of ferroelectric material was used for the Ferroelectric Fast Reactive tuner (FE-FRT) development. In a world first, CERN has tested the prototype FE-FRT with a superconducting cavity, and frequency tuning has been successfully demonstrated.Conclusion. Recent results on the development and experimental testing of advanced dielectric materials for accelerator applications are presented. Low loss microwave ceramics, quartz and CVD diamond are considered. We presented our experimental results on wakefield generation in microwave frequency ranges with the dielectric based accelerating structures. Special attention was paid to the experimental results on high power testing at X-band of the externally powered dielectric based components. Finally, we present here first experimental demonstration of ferroelectric tunable microwave ceramic for accelerator application, which includes both tunable dielectric wakefield accelerating structure and ferroelectric based fast high power tuner for superconducting cavities. The experimental results presented here are critical for the advanced dielectric wakefield accelerating structures and other components development intended for the future linear collider projects.